PENGARUH KANDUNGAN LEMPUNG DAN KADAR AIR TERHADAP COHESI DAN PHI TANAH LANAU BERLEMPUNG - Endaryanta Endaryanta (Universitas Negeri Yogyakarta, 2006)
ABSTRACTIn this year, landslide disaster such as embankment slide, bankslide, or buried of soil (trash) often occurs. All of them begin with asimple problem, that is infiltration of rain water (or other) into soil causingthe decrease of shear strength, finally passed the limit of landslide safetyfactor F, so landslide occurs. The research tries to know the behavior ofclayey-mud soil with several ratio of clay content and several watercontent ratio to find out how much clay content and water content (w)may induce soil collapse.This experiment research was conducted in the soil laboratoryUNY using clayey-mud soil from Klaten which has been conditioned inseveral clay content (00/0-400/0) and water content w (20%-30%) andthen direct shear tests were applied. The product of this experimentwere: cohesion (c), internal soil shear angle, phi (p), and safety factor oflandslide (F).This research has resulted: (1) For pure mud soil, until 25% watercontent, would decrease of cohesion (interlocking), but 25% watercontent,interlocking (cohesion) would constant. The maximum cohesion(interlocking)(0.09 kg/cm2) reaches at 20% of water content (2) Forpure mud soil, increasing of water content until 30% would increase of pand F. The maximum p value (41.8°) occur at 30% water content (at 0%clay content); (3) For clayey-mud soil, increasing of water contentcauses increasing or constant of cohesion. The cohesion would increaseif 10%-20% clay content. The c value until 0.0665 kg/cm2 at 30% watercontent (at 100/0 clay content); and (4) For clayey-mud soil, increasing ofwater content (until 25%) would increase of p and F. The p value coulduntil 40.9° at w=25% (at 10% clay content). If w25%, the value of pand F would decrease. The p value until 7.7° at w=300/0 (at 40% claycontent).Keywords: mud. clay, soil, water content, cohesion,landslide.